CAUSALITY IN HISTORICAL EXPLANATION - Ahmad Choirul Rofiq (JUSAN: Jurnal Sejarah Peradaban Islam Indonesia, 2023)
Based on the relevant works of historical methodology and Islamic history, this library research concludes that historical explanation is a scientific effort to seek historical reconstruction and explain causality linkages in various historical occurrences. The causality analysis is similar to the rule of regularity in historical explanation. The monocausal analysis seeks to find the ultimate cause of all causes by hierarchically arranging some causes and determining the most dominant cause. On the other hand, the multicausal analysis seeks to find the diversity of causes by placing all causes in an equally important position. The conflict between the Umayyad Dynasty and the Abbasid Dynasty (supported by the Mawali or non-Arab society) was monocausal because of rampant injustice due to oppression and discrimination by the Umayyads. The conflict between Abu Bakr's caliphate and the perpetrators of riddah after the Prophet PBUH died was multicausal due to various factors behind their dispute.